Student Activity Oriented Learning (PBAS) Against Students' Poetry Reading Ability - Dewirsyah, Amnur Rivai (Holistic Science, 2023)
This study aims to determine the effectiveness of student activity-oriented learning strategies on students' ability to read poetry. This research was conducted at the YWKA Medan Private Vocational School which is located on Jalan Bengkel, Pulo Brayan Village, Medan City. The population of this study were all class X BM students at YWKA Private Vocational Schools in the 2019/2020 Academic Year. The sample taken was class X majoring in Business Management at SMK YWKA for the 2019/2020 Academic Year with a total of 30 students. The method used in this research is a quantitative research method. Research Instruments are tools used to collect research data. To obtain data in the research, a data collection tool called an instrument was used in the form of an oral test to measure students' ability to read poetry. Based on the pretest results, the average value was 68.67 and the post-test results obtained an average value of 77.30. Thus, it can be concluded that "There is effectiveness in the ability to read poetry by class X BM BM YWKA Private Vocational Schools for the 2019/2020 Academic Year